The achievements and potential problems of digital and commmercial banks, solutions regarding to this case in the digital economy environment in Uzbekistan - Ashurakhunov , Abdufattokh (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This article analyzes the achievements and challenges of Uzbekistan's commercial banks in the context of the digital economy and the growing use of artificial intelligence. It evaluates how digitalization and AI-based systems have enhanced efficiency, accessibility, and innovation in banking operations while also creating new risks related to cybersecurity, data management, and regulatory adaptation. The study discusses examples from leading digital institutions and proposes strategic and policy recommendations to support sustainable, inclusive, and secure digital financial development in Uzbekistan.